2006
DOI: 10.1111/j.0014-3820.2006.tb00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Genetic Architecture Under Directional Selection

Abstract: We investigate the multilinear epistatic model under mutation-limited directional selection. We confirm previous results that only directional epistasis, in which genes on average reinforce or diminish each other's effects, contribute to the initial evolution of mutational effects. Thus, either canalization or decanalization can occur under directional selection, depending on whether positive or negative epistasis is prevalent. We then focus on the evolution of the epistatic coefficients themselves. In the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 54 publications
(59 reference statements)
0
95
0
Order By: Relevance
“…Prior theoretical work indicated that directional epistasis can facilitate the directional response of a population to selection [15,18]. Our model of epistasis that assumes independent effects ( f ¼ 0) is different from the model in references [15,18], which assumed a directional form of epistasis, such that alleles on average reinforce or suppress the effect of other alleles.…”
Section: Discussionmentioning
confidence: 97%
“…Prior theoretical work indicated that directional epistasis can facilitate the directional response of a population to selection [15,18]. Our model of epistasis that assumes independent effects ( f ¼ 0) is different from the model in references [15,18], which assumed a directional form of epistasis, such that alleles on average reinforce or suppress the effect of other alleles.…”
Section: Discussionmentioning
confidence: 97%
“…This appears not to be the case in analysis of statistical epistasis (Barton and Turelli 2004, Carter et al 2005, Hansen et al 2006. Again, this is because we focus on initial perturbation of functional epistasis.…”
Section: Discussion and Numerical Treatmentmentioning
confidence: 97%
“…As pointed out by Hansen et al (2006), the evolution of epistasis is not part of the corpus of classical population genetics. The statistical framework, exemplified by the recent work of Hansen et al, defines epistasis with respect to a reference genotype.…”
Section: Discussion and Numerical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of epistasis is a topic largely absent from classical population genetic literature (Hansen et al, 2006). The subject has, however, received increased attention in the past decade as relevant data on haploid genetic systems have become available Lenski 1997, 2001;Wilke and Adami 2001;You and Yin 2002;Sanjuan et al 2004;Bonhoeffer et al 2004;Burch and Chao 2004;Shapiro et al 2006).…”
Section: Introductionmentioning
confidence: 99%